2006
DOI: 10.1097/01.mat.0000249041.52862.fa
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Prophylactic Peritoneal Dialysis in Neonates and Infants After Complex Congenital Cardiac Surgery

Abstract: Peritoneal dialysis after complex congenital cardiac surgery was introduced to a group of neonates and infants (n = 756; age, 0 to 1 year) between May 1993 and December 2005. Indications of peritoneal dialysis were determined as well as methods, prolonged dialysis, and its outcomes. Demographic characteristics, preoperative risk factors, intraoperative variables, and postoperative complications were compared in 756 cases with ages below 1 year. All cases underwent ultrafiltration during the perioperative stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 19 publications
4
46
2
1
Order By: Relevance
“…14,19 Most of the complications of PD are minor and easily manageable. 9,10,15 The complications of PD detected in this study were similar to those seen in other reports, consisting primarily of infection and catheter malfunction. 24,25 The reported complications in catheter functioning are around 30%, nearly 2% being major complications, of the catheters inserted in their pediatric patients which is nearly identical with our cohort (30.3%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…14,19 Most of the complications of PD are minor and easily manageable. 9,10,15 The complications of PD detected in this study were similar to those seen in other reports, consisting primarily of infection and catheter malfunction. 24,25 The reported complications in catheter functioning are around 30%, nearly 2% being major complications, of the catheters inserted in their pediatric patients which is nearly identical with our cohort (30.3%).…”
Section: Discussionsupporting
confidence: 87%
“…The glomerular filtration rate is reduced in newborns compared with that of older infants. 9,10 Renal vascular resistance is high with correspondingly elevated circulating renin levels. Hormonal responses to volume loading including atrial natriuretic factor may also be limited in the newborn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference on AKI incidence in adult or pediatric patients following heart surgery is due to the more complex surgeries for congenital defects corrections. Alkan et al (29) describe that younger patients, more complex cardiac defects, longer extracorporeal circulation, and lower heart output are risk factors for AKI. In this context, they propose using a prophylactic PD catheter in newborns or infants undergoing complex heart surgery.…”
Section: Discussionmentioning
confidence: 99%
“…37 Alkan et al and Flynn reported that Peritoneal dialysis remains an effective modality for the management of pediatric AKI. 38,39 Complications of PD include bladder and bowel perforation, along with bleeding issues related to the procedure. 8 Peritonitis was not seen in our patients.…”
Section: Discussionmentioning
confidence: 99%